Peran Pokdarwis Andang Taruna Sebagai Katalisator Terwujudnya Karakter Peduli Wisata (Studi Di Banraas Pulau Gili Iyang Madura) - Enza Resdiana; Laylatul Hasanah (Journal of Governance Innovation, 2020)
Tourism Awareness Group or abbreviated Pokdarwis is a self-help and self-help group that grows from, by and for the community and aims to enhance the development of regional tourism and succeed tourism development by becoming a government partner in raising public awareness in the field of tourism, increasing human resources, encouraging the realization of Sapta Enchantment, enhancing the quality of products and tourism. This research uses descriptive qualitative method, which is the subject and object of this research is the Tourism Awareness Group (Pokdarwis) of Andang Taruna Banraas Village. Tourism Care (Study in Banraas, Gili Iyang Madura Island). The role of Pokdarwis Andang Taruna is able to act as a mobilizer for the community where the community has provided support and role as host in efforts to create an environment and conducive atmosphere that is able to encourage the growth and development of the tourism industry and the realization of sapta charm. The role as a partner has been carried out by Pokdarwis Andang Taruna in the form of activities and programs carried out by involving the Government and other parties related to the development and construction of tourist facilities such as lodging, transportation, culinary and etc. although there has not been a maximum cooperation between Pokdarwis and the Government so that there are obstacles in realizing the character of caring tourism.